Administration of hydrogen sulfide via extracorporeal membrane lung ventilation in sheep with partial cardiopulmonary bypass perfusion: A proof of concept study on metabolic and vasomotor effects - Derwall, Matthias; Francis, Roland C. E.; Kida, Kotaro; Bougaki, Masahiko; Crimi, Ettore; Adrie, Christophe; Zapol, Warren M.; Ichinose, Fumito (Critical Care, 2011)
Introduction: Although inhalation of 80 parts per million (ppm) of hydrogen sulfide (H2S) reduces metabolism in mice, doses higher than 200 ppm of H2S were required to depress metabolism in rats. We therefore hypothesized that higher concentrations of H2S are required to reduce metabolism in larger mammals and humans. To avoid the potential pulmonary toxicity of H2S inhalation at high concentrations, we investigated whether administering H2S via ventilation of an extracorporeal membrane lung (ECML) would provide means to manipulate the metabolic rate in sheep.Methods: A partial venoarterial cardiopulmonary bypass was established in anesthetized, ventilated (fraction of inspired oxygen = 0.5) sheep. The ECML was alternately ventilated with air or air containing 100, 200, or 300 ppm H2S for intervals of 1 hour. Metabolic rate was estimated on the basis of total CO2 production (V̇ CO2) and O2 consumption (V̇ O2). Continuous hemodynamic monitoring was performed via indwelling femoral and pulmonary artery catheters.Results: V̇ CO2, V̇ O2, and cardiac output ranged within normal physiological limits when the ECML was ventilated with air and did not change after administration of up to 300 ppm H2S. Administration of 100, 200 and 300 ppm H2S increased pulmonary vascular resistance by 46, 52 and 141 dyn·s/cm5, respectively (all P ≤ 0.05 for air vs. 100, 200 and 300 ppm H2S, respectively), and mean pulmonary artery pressure by 4 mmHg (P ≤ 0.05), 3 mmHg (n.s.) and 11 mmHg (P ≤ 0.05), respectively, without changing pulmonary capillary wedge pressure or cardiac output. Exposure to 300 ppm H2S decreased systemic vascular resistance from 1,561 ± 553 to 870 ± 138 dyn·s/cm5 (P ≤ 0.05) and mean arterial pressure from 121 ± 15 mmHg to 66 ± 11 mmHg (P ≤ 0.05). In addition, exposure to 300 ppm H2S impaired arterial oxygenation (PaO2 114 ± 36 mmHg with air vs. 83 ± 23 mmHg with H2S; P ≤ 0.05).Conclusions: Administration of up to 300 ppm H2S via ventilation of an extracorporeal membrane lung does not reduce V̇ CO2 and V̇ O2, but causes dose-dependent pulmonary vasoconstriction and systemic vasodilation. These results suggest that administration of high concentrations of H2S in venoarterial cardiopulmonary bypass circulation does not reduce metabolism in anesthetized sheep but confers systemic and pulmonary vasomotor effects. © 2011 Derwall et al.; licensee BioMed Central Ltd.
CRIS-Team Scopus Importer:2022-11-17